Prediction of drug-carrier interactions of PLA and PLGA drug-loaded nanoparticles by molecular dynamics simulations. (15th March 2021) - Stipa, Pierluigi; Marano, Stefania; Galeazzi, Roberta; Minnelli, Cristina; Mobbili, Giovanna; Laudadio, Emiliano
Graphical abstract: Highlights: PLGA has a greater affinity to water than PLA, which preferentially interacts with itself. Paracetamol molecules interact at the polymer-water interface. Prednisolone shows high affinity for polymers' cores due to strong hydrophobic interactions. Isoniazid totally dissolves in the aqueous phase diffusing out from the polymers' cores. Abstract: In the field of drug delivery, biodegradable polymeric nanoparticles have attracted a great deal of research interest due to their potential as an ideal non-toxic vehicle for the delivery of active compounds in a controlled and targeted manner. However, at the stage of academic and industrial development, the lack of regulatory instructions for the assessment and characterization of those nanometric materials is considerably delaying their clinical success if compared to other macroscopic systems (i.e. microparticles). In fact, owing to their high surface area to volume ratio, unwanted interactions between nanoparticles and biological systems may occur, leading to unexpected toxicity. In addition, knowledge of drug-polymer interactions is compulsory, as they can directly affect many fundamental properties, such as the drug-loading ability, nanoparticle size, the drug physical state and stability, as well as the actual drug release profile. In this context, computational methods able to rapidly predict the binding and dynamics between drug molecule and its carrier, and between the carrier and biological systems, are highly desirable to minimize the investment in drug design and development. In this study a full atomistic molecular dynamics simulation approach was validated to investigate biomolecular behaviour of poly (lactic acid) (PLA) and poly (lactic-co-glycolic acid) (PLGA) as nanoparticulate drug delivery systems. Both polymer systems have been firstly investigated without drugs to better observe their tendency to interact with aqueous solution, which represents a crucial point for drug delivery systems. Subsequently, simulations were run after the incorporation of drugs. Paracetamol, Prednisolone, and Isoniazid were chosen as model drugs in relation to their different affinity with lipids. Specific interactions between polymers and drugs were considered, and a direct comparison between computational results and experimental evidences found in literature was carried out.